Bifunctionalization of Polyoxometalates with Two Different Organoimido Ligands. Issue 4 (19th December 2012) - Lv, Chunlin; Khan, Rao Naumaan Nasim; Zhang, Jin; Hu, Junjie; Hao, Jian; Wei, Yongge
<x xml:space="preserve">Abstract</x> Doubly modified: Polyoxometalates can incorporate a large number of different functionalities in a way that mixes the ligands in a one‐pot reaction. A class of mixed organoimido bifunctionalized hexamolybdates is presented that involves two different moieties L1 and L2, namely, differing aromatic, aromatic and aliphatic, and aliphatic moieties.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>